CLARA: an integrated clinical research administration system. (28th April 2014) - Bian, Jiang; Xie, Mengjun; Hogan, William; Hutchins, Laura; Topaloglu, Umit; Lane, Cheryl; Holland, Jennifer; Wells, Thomas; Fan, Yu; Baker, Matt; Jiawei, Yuan
Abstract: Administration of human subject research is complex, involving not only the institutional review board but also many other regulatory and compliance entities within a research enterprise. Its efficiency has a direct and substantial impact on the conduct and management of clinical research. In this paper, we report on the Clinical Research Administration (CLARA) platform developed at the University of Arkansas for Medical Sciences. CLARA is a comprehensive web-based system that can streamline research administrative tasks such as submissions, reviews, and approval processes for both investigators and different review committees on a single integrated platform. CLARA not only helps investigators to meet regulatory requirements but also provides tools for managing other clinical research activities including budgeting, contracting, and participant schedule planning.